Perintah Belajar dan Mengajar dalam Q. S. Al-‘Alaq Ayat 1-5 Menurut Tafsir Ath-Thabari - Putri, Ayilzi; Alfiansyah, Muhammad; Panjaitan, Siti Aisyah; Siregar, Alde Rizky Pratama; Br Ginting, Aloken Marwahta (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2023)
This research explains about teaching and learning commands in QS. Al-'Alaq verses 1-5 according to the interpretation of Ath-Thabari. The type of research in this paper is descriptive qualitative. As for obtaining concrete and appropriate data in this study using literature study techniques. This research was written with the formulation of the problem how the concept of learning and teaching commands according to the Al-Qur'an surah Al-'Alaq verses 1-5 according to the interpretation of Ath-Thabari. The results of this study indicate that the verses in surah Al-'Alaq emphasize the importance of reading, seeking knowledge, and gaining better understanding through the learning process. Allah commands people to recite in the name of their Lord, indicating that the knowledge acquired must be related to truth and faith in Allah. So that from this research it can be concluded that the concept of learning and teaching commands in Surah Al-Alaq verses 1-5 according to the interpretation of aht-Thabari emphasizes the importance of reading, seeking knowledge, and obtaining correct understanding in Islam. It underscores the values of education, writing and dissemination of knowledge in the context of spiritual development and societal development.Keywords: learning, teaching, al-'alaq 1-5, ath-thabari